A model for incorporating specialist nurse education into a university context. Part 1: Methodological perspectives - Judith C. Bruce; Hester C. Klopper (AOSIS, 2010)
The education of nurses for specialist practice takes place mainly in nursing colleges. In view of ongoing debates about the future positioning of nursing education, an investigation regarding the incorporation of college-based specialist nurse education into universities was needed. The purpose of the study was to develop and describe a model for specialist nurse education in a university. The objectives were set in two phases: Phase 1 objectives were designed to enable the identifcation of concepts in relation to university education and Phase 2 objectives, to enable the development of a model for specialist nurse education in a university context. This paper gives an account of only the methodology used to meet the research purpose and objectives. It outlines the objectives of Phases 1 and 2, including a detailed description of the research design. In discussing the research design, particular attention was given to theory development. The research methods were described with reference to data collection methods and procedures, study samples and sampling methods, data analysis methods and processes, to ensure the trustworthiness of the study. The model is described in Part 2 of the article. Opsomming Die onderrig van verpleegkundiges in gespesialiseerde verpleegpraktyk vind hoofsaaklik in verpleegkolleges plaas. In die lig van die voortslepende debat rondom die toekomstige posisionering van verpleegonderrig is ondersoek na die inkorporering van spesialis vepleegopleiding aan universitieite as noodsaaklik geag. Die doel van hierdie studie was om die model vir gespesialiseerde vepleegopleiding aan universitiete te ontwikkel en te beskryf. Die navorsingsdoelwitte is geformuleer aan die hand van twee fases. Die doelwitte in Fase 1 was ontwerp om die konsepte betreffende universiteitsopleiding te identifseer. Die doelwitte in Fase 2 was op die ontwikkeling van 'n model vir die onderrig in gespesialiseerde verpleegkunde aan 'n universiteit gerig. Hierdie artikel gee 'n oorsig oor slegs die metodiek wat gebruik is om die doel en navorsingsdoelwitte te bereik. Dit verskaf 'n oorsig oor Fase 1 en 2 en sluit 'n omvattende beskrywing van die navorsingsontwerp in. In die bespreking van die navorsingsontwerp word spesifeke aandag aan teoriegenerering gewy. Die navorsingsmetodes word beskryf met verwysing na data insamelingsmetodes-en-prosedures, die steekproef, en steekproefmetodes, data analiseringsmetodes-en-prosedures wat die betroubaarheid van die studie verseker het. Die model word in Deel 2 van die artikel beskryf.